SISTEM INFORMASI PENGELOLAAN DATA BERBASIS WEB PADA POS KESEHATAN DESA GARUNTUNGAN KABUPATEN BULUKUMBA - Risda Ariyanti; Dedy Hendryadi; Juniarti Iryani (Institut Teknologi dan Bisnis Bina Adinata, 2023)
Abstrak - This study aims to:(1) design a web-based data management information system at the Garuntungan village health post, Bulukumba district. (2) implement a web-based data management information system at the Garuntungan village health post, Bulukumba district. (3) how is the user's response to the web-based data management information system at the village health post. This study uses the waterfall method. This method uses 6 stages, namely, Analysis, Design, Coding, Testing, Implementation, Maintenance This research produced a web-based data management information system at the Garuntungan village health post, Bulukumba district, which can be used on computers and can also be used on Android smartphones. In this study, an instrument was used in the form of a questionnaire to find out the user's response, namely, employees at the Garuntungan Village Health Pod. Based on the response from Garuntungan village health post employees after using this system, that is, overall it looks attractive, besides that this system is also very helpful regarding data management, especially patient and drug data, and this application is also very helpful in the process of recording existing data at the health post this village. The value obtained from the results of data analysis is 90 with a very positive category